Krisis Ekologi dan Mandat Kekhalifahan dalam Hukum Lingkungan Qur’ani (CV. Era Digital Nusantara, 2025)
Ecological crisis in Indonesia poses severe threats to environmental sustainability and human survival. This study examines how Qur'anic principles of khalifah (stewardship), mizan (equilibrium), fasad (corruption/destruction), and amanah (trustworthiness) provide comprehensive ethical frameworks for environmental protection in Islamic law. Through qualitative textual analysis integrating Qur'anic exegesis with contemporary environmental jurisprudence (fiqh al-bi'ah), the research investigates the applicability of Islamic environmental law to Indonesia's ecological challenges, particularly the 2025 Sumatra floods resulting from long-term deforestation. The study analyzes maqasid al-Shariah's principle of environmental preservation (hifz al-bi'ah) and demonstrates how Islamic environmental law can be integrated with Indonesia's positive environmental law system. While the Indonesian Ulema Council's green fatwas provide moral and normative frameworks, implementation faces challenges due to legal dualism and weak institutional enforcement. The research concludes that effective environmental protection requires systematic integration of Islamic environmental principles with state legal mechanisms, complemented by community-based approaches emphasizing spiritual values and moral responsibility toward nature as manifestation of obedience to God.